Prvo opazovanje kraljičice Phylloscopus proregulus v Bolgariji in verjetno razlogi za njeno povečano pojavljanje v Evropi - Nankinov, Dimitar (Acrocephalus, 1999)
Pallas's Leaf Warbler (Phylloscopus proregulus) was observed in the centre of Sofia, one individual on November 6th 1997 and two on the following day. Information about its characteristic features and behaviour is given. The phenomenon of the influx by this species in Europe is discussed. From the so far published information we can conclude that the Pallas's Leaf Warbler reaches Europe between September 5th and November 30th and stays there during the winter and spring. We suppose that Europe is penetrated by the birds from the late hatches and those that stay in their nesting places somewhat longer in the autumn. Such birds fall under the influence of the anticyclones, which build up during the September-November period in Siberia, so that they are driven to Europe.
Keywords: Birds; ornitologija; ptice; bird; Ecosystem; opazovanje; Bulgaria